Application of [Hydroxy(tosyloxy)iodo]benzene in the Wittig-Ring Expansion Sequence for the Synthesis of Î²-Benzocyclo-alkenones from Î±-Benzocycloalkenones - G. Koser (Molecules, 2005)
The conversion of Î±-benzocycloalkenones to homologous Î²-benzocyclo-alkenones containing six, seven and eight-membered rings is reported. This wasaccomplished via a Wittig olefination-oxidative rearrangement sequence using[hydroxy(tosyloxy)iodo]-benzene (HTIB) is the oxidant, that enables the synthesis ofregioisomeric pairs of methyl-substituted Î²-benzocycloalkenones. The incorporation ofcarbon-13 at C-1 of the Î²-tetralone nucleus was also demonstrated. The Wittig-HTIBapproach is a useful alternative to analogous sequences in which Tl(NO3)3Â·3H2O or thePrevost combination (AgNO3/I2) are employed in the oxidation step.